Using hypnosis to enhance self-efficacy in sport performers - Barker, J. B.; Jones, M. V.; Greenlees, I. (Journal of Clinical Sport Psychology, 2013)
High levels of self-efficacy have been documented to be associated with optimal levels of sport performance. One technique, which has the potential to foster increased self-efficacy, is hypnosis. Hypnosis is based upon the power of suggestion and, while often shrouded in myth and controversy, has been used in a number of domains including medicine, dentistry, and psychotherapy. In contrast, sport psychology is one domain where the use of hypnosis has yet to be fully explored. The aim of this review is to add to the extant literature and delineate how hypnosis potentially can enhance self-efficacy. By drawing on neodissociation and nonstate theories of hypnosis, a combined theoretical basis is established to explain how hypnosis may be used to influence sport performers` sources of self-efficacy information. Furthermore, the review examines these theoretical postulations by presenting contemporary research evidence exploring the effects of hypnosis on sport performers` self-efficacy. The review concludes with future research directions and suggestions for sport psychologists considering the use of hypnosis within their practice.